2021
DOI: 10.31235/osf.io/qw249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence, Teacher Tasks and Individualized Pedagogy

Abstract: This paper investigates how educational technologies that use different combinations of artificial and human intelligence are incorporated into classroom instruction, and how they ultimately affect learning. We conducted a field experiment to study two technologies that allow teachers to outsource grading and feedback tasks on writing practices of high school seniors. The first technology is a fully automated evaluation system that provides instantaneous scores and feedback. The second one uses human graders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…On the other hand, AWE systems are helping teachers in auto grading, evaluating, and providing feedbacks to students. Ferman et al (2021) observed that the results of AWE systems are consistent with teachers at routine tasks, and require low skills to run. The authors also arguably stated that an advanced AWE is a better substitute for accomplishing language teachers' most complex and routine tasks.…”
Section: Risk In Shifting Teacher's Rolementioning
confidence: 67%
“…On the other hand, AWE systems are helping teachers in auto grading, evaluating, and providing feedbacks to students. Ferman et al (2021) observed that the results of AWE systems are consistent with teachers at routine tasks, and require low skills to run. The authors also arguably stated that an advanced AWE is a better substitute for accomplishing language teachers' most complex and routine tasks.…”
Section: Risk In Shifting Teacher's Rolementioning
confidence: 67%
“…Upon automated feedback, the writing samples go to an interface where teachers make additional comments and assign grades in real-time. An evaluation of the innovation across 178 secondary schools is currently underway (J-PAL, n.d.; Bruno, Lima, & Riva, 2021).…”
Section: Opportunities Through Edtechmentioning
confidence: 99%